Development of Education Kit Prototype Based on Internet of Things (IoT) - Arsy Novita Syahada; Doli Aryo Dani Sinaga; Karlisa Priandana (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2021)
In answering the challenges of industrial revolution 4.0, robotics and the Internet of Things (IoT) should be used as one of the learning curricula at all educational stages, especially at the high school level. Furthermore, robotics and IoT education are now becoming an important aspect to implement and learn about Science, Technology, Engineering, and Mathematics (STEM) education. To support robotics and IoT education, an easy and user-friendly education kit as a learning medium is required. This work aims at developing a prototype of a robotics and IoT education kit that is suitable for senior high school students. The education kit is designed to be interesting and challenging enough to increase the student's interest in learning robotics and IoT. The kit is developed by using various independent and unattached sensors so that the users, i.e., high-school students can choose their sensors and can investigate the microcontroller pins that are used for these components. In addition, users can also learn to connect an electronic component with other electronic components on the kit to be able to produce various logical embedded systems that can be connected to the internet.